Evaluation of cholinesterase level in an endemic population exposed to malathion suspension formulation as a vector control measure - CS Lal; V Kumar; A Ranjan; VNR Das; N Kumar; K Kishore; SK Bhattacharya (Memorias do Instituto Oswaldo Cruz, 2004)
The manuscript describes a study on the blood cholinesterase (ChE) level in an exposed population at different interval of time after spraying with malathion suspension (SRES) use for kala-azar vector control in an endemic area of Bihar, India. The toxicity of a 5% malathion formulation in the form of a slow release emulsified suspension (SRES) was assessed by measuring serum ChE levels in spraymen and in the exposed population.The study showed a significant decrease in ChE levels in the spraymen (p < 0.01) after one week of spraying and in exposed population one week and one month after of spraying (p < 0.01), but was still within the normal range of ChE concentration, one year after spraying, the ChE concentration in the exposed population was the same as prior to spraying (p > 0.01). On no occasion was the decrease in ChE level alarming. A parallel examination of the clinical status also showed the absence of any over toxicity or any behavioural changes in the exposed population. Hence, it may be concluded that 5% malathion slow release formulation, SRES, is a safe insecticide for use as a vector control measure in endemic areas of kala-azar in Bihar, India so long as good personal protection for spraymen is provided to minimize absorption and it can substitute the presently used traditional DDT spray.